A proposta de uma ética da responsabilidade para a civilização tecnológica em Hans Jonas - Lima, Valéria Cassandra Oliveira de (2009)
This study examines the proposal for an ethics of responsibility in Hans Jonas, and constitutes it as a north in the solution to the problem of ethical proposal. In the present context, it was established a foundational crisis of moral and, at the same time, a need of reasoning of the moral judgments, considering the existing ethical vacuum in the pluralistic and secularized humanity. In this perspective, the search for a value in itself should constitute the most fundamental character of an ethical proposal. Jonas identifies this value in itself in life, that is, the existence of an authentic life in the future. An ethics for the technological civilization must differentiate itself from the view of nature as an object indifferent to the ethical positioning, thus it is urgent a new ethical posture according to the modifying character of human actions. The threat of an absence of existence is likely to be constituted as a compass for this new in the field of ethics, this malum is what Hans Jonas calls the "heuristic of fear" and this unleashes that what is at stake is the integrity of the human essence itself. The idea of duty and of human conduct properly guides the moral, but one can not talk about moral and human conduct without the presence of the man in the world as a primary and primordial datum. The presence of life in the world has become a duty. The justification for such ethics is the acclaim of an unconditional imperative that is the authentic existence in the future, as well as search for an ethical reasoning in the Being and in the value of life in its general appearance. The goal with this feat is to overcome the subjectivism of values and to implement an ethics beyond the intersubjective space. For this to occur, it is introduced more effectively the concept of responsibility within the sphere of morality. Diverting the ethical aspect from the momentary act itself, ethics is established in the actions and their causal projections for the future, taking into account long-term impact and irreversible acts.